E-marketing by Mobile Apps for Tourism Products and Its Impact on the Performance of Travel and Tourism Organizations - Nabil Mohemmed Al-Hazmi (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This study seeks to study E-marketing by mobile Apps for tourism products and its impact on the performance of travel and tourism organizations in Al-Kharj Governorate. The research dealt with scientific and theoretical analysis. The descriptive method of analysis was used to conduct this study. Moreover, a special questionnaire form was distributed and was designed to the (200) study sample organizations. The study ended up with the presence of an impact of E-Tourism Marketing at the level of services provided by tourism organizations in Al-Kharj Governorate, and provided important recommendations, the most important of which is to work on providing the infrastructure for E- Marketing by mobile apps technology to allow for the provision of the best services among tourism service providers and those who are in charged in providing them.